2009
DOI: 10.1007/s00415-009-5228-x
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein in the very early phase of acute ischemic stroke: association with poor outcome and death

Abstract: Acute ischemic stroke may trigger an inflammatory response that leads to increased levels of C-reactive protein (CRP). High levels of CRP may be associated with poor outcome because they reflect either an inflammatory reaction or tissue damage. We evaluated the prognostic value of CRP within 12 h of onset of ischemic stroke. Levels of CRP were routinely obtained within 12 h of symptom onset in 561 patients with ischemic stroke. CRP values were dichotomized as <7 or ≥7 mg/L. The full range of CRP values was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 30 publications
10
78
1
3
Order By: Relevance
“…Studies have shown that CRP was strongly associated with the prognostic outcome after AIS (1,19,24,25). Ormstad et al (1) found that CRP played an important role in the progression of cerebral tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CRP was strongly associated with the prognostic outcome after AIS (1,19,24,25). Ormstad et al (1) found that CRP played an important role in the progression of cerebral tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Age was categorized as <50, 50-59, 60-69, 70-79 and ≥80 years. The level of CRP was categorized as <7mg/L and ≥7mg/L (Due to the skewed distribution of CRP, we chose a somewhat arbitrary cut off point for CRP: values below 7mg/L were considered normal) 11 . National Institutes of Health Stroke Scale values were dichotomized at 8, which was considered as relatively severe illness 12 .…”
Section: Baseline Variablesmentioning
confidence: 99%
“…(16) In our study, we found 63.3% of total subjects with ischemic stroke have high levels of hsCRP (>3 mg/L) and mean of hsCRP in total subjects are 10.5 mg/L ( Table 1) (18) On the other hand, only 22% of stroke patients had high CRP (>7 mg/L) levels in a study from Netherlands. (19) This variance may be explained partly by the different definitions of high CRP in various studies. In addition, cohort study of stroke patients with median of 10 days after stroke onset demonstrated an association between higher levels of IL-6, CRP and fibrinogen and an increased incidence of recurrent stroke.…”
Section: Research Subjectsmentioning
confidence: 99%